Conceptual replication and extension of health behavior theories' predictions in the context of COVID‐19: Evidence across countries and over time - Georgios Abakoumkin (562723) (2023)
Virus mitigation behavior has been and still is a powerful means to fight the COVID‐19 pandemic irrespective of the availability of pharmaceutical means (e.g., vaccines). We drew on health behavior theories to predict health‐protective (coping‐specific) responses and hope (coping non‐specific response) from health‐related cognitions (vulnerability, severity, self‐assessed knowledge, efficacy). In an extension of this model, we proposed orientation to internal (problem‐focused coping) and external (country capability) coping resources as antecedents of health protection and hope; health‐related cognitions were assumed as mediators of this link. We tested these predictions in a large multi‐national multi‐wave study with a cross‐sectional panel at T1 (Baseline, March‐April 2020; N = 57,631 in 113 countries) and a panel subsample at two later time points, T2 (November 2020; N = 3097) and T3 (April 2021; N = 2628). Multilevel models showed that health‐related cognitions predicted health‐protective responses and hope. Problem‐focused coping was mainly linked to health‐protective behaviors (T1‐T3), whereas country capability was mainly linked to hope (T1‐T3). These relationships were partially mediated by health‐related cognitions. We conceptually replicated predictions of health behavior theories within a real health threat, further suggesting how different coping resources are associated with qualitatively distinct outcomes. Both patterns were consistent across countries and time. Other Information Published in: Social and Personality Psychology Compass License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/spc3.12909